Heat transfer improvement in turbulent flow using detached obstacles in heat exchanger duct - Omar Ghoulam; Hind Talbi; Kamal Amghar; Abdel-illah Amrani; Adil Charef; Ismael Driouch (International Journal of Thermofluids)
The current study aims to enhance the effectiveness of a cooling system by introducing vertical and detached obstacles within a rectangular channel to create singularities in the flow. This study focuses on a numerical simulation to investigate the effects of these detached obstacles on forced convective airflow (cooling fluid) in a turbulent flow within a heat exchanger's rectangular channel. The mathematical model governing the fluid flow and heat transfer is based on the Finite Volume Method (FVM) and solves the Navier-Stokes equations under the assumption of steady-state, incompressible flow with constant fluid properties. Two types of obstacles were considered: planar (Type A) and diamond-shaped (Type B), with four different spacings (S = s/2, S = s, S = 5s/4, and S = 3s/2). The simulations were carried out for Reynolds numbers (Re) ranging from 20,000 to 35,000. The CFD calculations employed the SIMPLE algorithm with the QUICK scheme for discretizing the governing equations. The analysis included the impact of obstacle geometry and spacing on hydrothermal interactions, focusing on axial velocity, dynamic pressure, local and average Nusselt numbers, friction factor, and thermal enhancement factor. The results show that diamond-shaped obstacles significantly outperform planar obstacles in terms of both hydrothermal performance and thermal enhancement. Additionally, increasing the distance between the detached obstacles leads to a higher average Nusselt number.